Distribution of microsporidia in preterm and full-term infant gut microbiomes and implications for host health - Sarkar, Anujit; Groer, Maureen; Ho, Thao T. B.; Dishaw, Larry J. (Frontiers in Pediatrics, 2025)
BackgroundMicrosporidia are a group of single-celled fungi which infect various chordates including humans, where they mainly pose a risk to immunocompromised individuals. This study aimed to investigate the occurrence of microsporidia in groups of very low birth weight (VLBW) and extremely low birth weight (ELBW) infants, comparing the findings with a publicly available dataset of term infant samples.MethodsMetagenomic sequencing was conducted on stool samples from two cohorts of preterm infants: cohort 1, which included 10 samples collected at 2, 4, and 8 weeks, and cohort 2, which consisted of 12 samples taken at 6 weeks and 2 years. These results were compared with data from a previously published cohort of term infants (cohort 3), which had 19 samples (in duplicates) collected between 1 and 14 weeks. Microsporidia identified from the data were separated and principal component analysis (PCA) was utilized to compare the microbiome of term and preterm infants. Microsporidia species that were significantly different between the two groups were identified using ALDEx2.ResultsEarly-stage microsporidia distribution did not show significant differences between the cohorts. However, significant differences emerged as the preterm infants grew, particularly at the age of 2 years (cohort 2). The levels of Mitosporidium daphniae (p = 0.03) and Nematocida homosporus (p = 0.04) were significantly higher in preterm infants compared to those born at term. Additionally, Encephalitozoon romaleae and Nosema ceranae, revealed an increase in cohort 2 from 6 weeks to 2 years.ConclusionsThis manuscript reports, to the best of our knowledge, the first occurrence of microsporidia in the early stages of human life. Some microsporidia not only persist into childhood but also become more prevalent during this time. However, we wish to emphasize that the findings from this study should be interpreted with caution, considering the low sample size and comparing cohorts examined at different time points of infants' age. Future studies with larger sample sizes and more mechanistic approaches could help clarify their role in childhood development and long-term health.